Pembelajaran Berkarakter dan Berinovasi Abad 21 Materi Fluida dengan Model Pembelajaran Project Based Learning pada SMK 1 Adiwerna - Ummi Rizani (Cakrawala: Jurnal Pendidikan, 2022)
Learning in the 21st century requires learning innovation must also produce quality learning models so as to facilitate the formation of human resources in accordance with global demands, namely the development of aspects: creative-productive thinking, decision making, problem solving, learning skills how to learn, collaboration skills, and processing. self-management. In the implementation of the PJBL model students are engaged in activities to solve problems and other meaningful tasks, provide opportunities for students to work autonomously, construct their own learning, and ultimately produce tangible products that are valuable, and realistic. The PjBL model also has advantages and disadvantages so it needs further study by comparing and analyzing other learning models that are more in accordance with the characteristics of students so that the learning objectives are achieved.